ANALISI YURIDIS TERHADAP PENGECUALIAN PEMBAKARAN LAHAN DAN HUTAN BERDASARKAN PASAL 69 AYAT (2) UNDANG-UNDANG NOMOR 32 TAHUN 2009 TENTANG PENGLOLAAN DAN PERLINDUNGAN LINGKUNGAN HIDUP - Gaol, Hendra Eriant Dikser Lumban; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Indonesia is a country rich in natural wealth. Among them are forests. According to Big Indonesian Dictionary, the forest is a land overgrown with trees and usually not maintained by people. Some types of forest in Indonesia according to climate is tropical rain forest, forest season, savanna, steppe and mangrove forest (mangrove). The type of forest based on its function is conservation forest, protection forest and production forest.Forest fires are frequent in Indonesia, especially on the islands of Sumatra and Kalimantan. In history it is said that forest fires have occurred in Indonesia since the 18th century. Starting from a fire in the forest area between the Kalanan River and Cempaka (now Sampit River and Katingan River) Central Kalimantan Province in 1877. Based on the above explanation, the author of this law provides a knowledge of a thing that should be raised into a study with Title "Juridical Analysis Against the Exemption of Land and Forest Burning Based on Article 69 Paragraph (2) of Law Number 32 Year 2009 on the Management and Protection of the Environment". With the issue What is the basis of consideration of the exception to forest fires according to Law Number 32 Year 2009 on Environmental Protection and Management? Is the exclusion not contrary to other laws and regulations? The type of research used by the author is normative juridical research, which is the type of research that discusses the principles of law, legal system, legal synchronization level, legal history and comparative law.As for the conclusions obtained from the research is that the basis of consideration of exception to forest fires according to law number 32 of 2009 on environmental protection and management to date is still a question. Taking into account only local wisdom, fires on forests and land are then allowed (exceptions). The Status of Exception The provision of Article 69 Paragraph (2) of the Other Laws and Regulations is clearly contradictory. This is particularly evident in Article 28H paragraph (1) of the 1945 Constitution of the State of the Republic of Indonesia.KEY WORDS: Law Enforcement, Forest and Landfire, Regulatory Synchronization